(untitled) (Sociología y tecnociencia, 2021)
With the singularity realization, this paper offers a review of the digital economy development and its impact in the labour relations and business culture. The paper studies the several stages and expressions: from the gig phase, with collaborative/shared and circular economy, autonomous and orange economy, to the wellbeing economics, with talent and happiness management). Through historical-comparative techniques and case studies, the results of the transformative initiatives and classifications realize by the large labour firms (Manpower, Adecco and Randstat) and the transnational consultant companies (GPTW, Deloitte and PWC), they are attended and contrasted, and mixed with collaborative intelligence and good practices from international forums (Global Compact-UN and Wellbeing Economics Alliance-WEF). In this way, a holistic vision of the model promoted by the leading actors in the digital transition and transformation of business and professional culture is offered according to Horizon 2030.